2011
DOI: 10.3945/ajcn.110.001784
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin A and zinc supplementation on treatment outcomes in pulmonary tuberculosis: a randomized controlled trial

Abstract: Supplementation with vitamin A and zinc did not affect treatment outcomes in participants with pulmonary tuberculosis at 8 wk. This trial was registered at controlled-trials.com as ISRCTN80852505.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 30 publications
1
56
0
1
Order By: Relevance
“…The study received ethical approval from the University of Cape Town ethics committee and was done in accordance with the Helsinki Declaration. The micronutrient intervention had no effect on the outcomes (26). A description of the primary study has been published (26).…”
Section: Study Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study received ethical approval from the University of Cape Town ethics committee and was done in accordance with the Helsinki Declaration. The micronutrient intervention had no effect on the outcomes (26). A description of the primary study has been published (26).…”
Section: Study Participantsmentioning
confidence: 99%
“…Patients were randomized to receive micronutrient or placebo intervention in a previously conducted prospective doubleblind controlled study of 154 patients from Cape Town, South Africa (26). The study received ethical approval from the University of Cape Town ethics committee and was done in accordance with the Helsinki Declaration.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that Cu, Zn and Cu/Zn were indirect pointers but not specifi c markers of TBC. Low concentrations of vitamin A and zinc are common in SVJETLANA LUTEROTTI 1 TONČICA VUKMAN KORDIĆ 2 IVKA ZORIČIĆ LETOJA 3 SLAVICA DODIG 3 sera of TBC patients. However, Visser et al (3) detected no eff ect of supplementation with vitamin A and zinc aft er an 8-week treatment.…”
mentioning
confidence: 99%
“…In addition to investigations dealing with adult patients (e.g., refs. [1][2][3][4][5][6], there are only a few papers dealing with childhood tuberculosis (7-10).…”
mentioning
confidence: 99%